2016
DOI: 10.1007/s13187-016-1053-y
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy, Mammogram Awareness and Screening Among Tertiary Hospital Women Patients

Abstract: In spite of high mortality rates and prevalence, breast cancer awareness and screening is low among Turkish women. This study aimed to determine level of health literacy, mammogram awareness, and screening among tertiary hospital women patients. A cross-sectional study was conducted with 519 patients aged between 40 and 69. A questionnaire was applied to women patients including demographic characteristics, health behaviors, mammogram awareness and screening, and health literacy tool. Mammogram awareness and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…With this study, we have demonstrated that Croatian women with average BC risk are not prone to taking over-the-counter drugs, and that they are significantly more concerned about the potential systemic and local side effects of the medication. Since these women have generally accurately assessed their BC risk, we hypothesize that they had a high level of health awareness, which is consistent with the literature data ( Yilmazel, 2018 ).…”
Section: Discussionsupporting
confidence: 87%
“…With this study, we have demonstrated that Croatian women with average BC risk are not prone to taking over-the-counter drugs, and that they are significantly more concerned about the potential systemic and local side effects of the medication. Since these women have generally accurately assessed their BC risk, we hypothesize that they had a high level of health awareness, which is consistent with the literature data ( Yilmazel, 2018 ).…”
Section: Discussionsupporting
confidence: 87%
“…Some studies indicated similar results (Maral, Budakoğlu, Özdemir, & Bumin, 2009;Yılmazel, 2016) while some others found no significant relationships between women's education level and having mammography done (Dişcigil, Şensoy, Tekin, & Soylemez, 2007;Seçginli & Nahçıvan, 2006). On the other hand, a study result showed that the knowledge of cervical cancer and the uptake of Pap smear screening are abysmally low among the women (Okunowo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…15 Yine üçüncü basamak bir hastanede, 40-69 yaş arası kadınlar ile yapılan bir çalışmada, katılımcıların SOY düzeyi REALM (Rapid Estimate of Adult Literacy in Medicine-Tıpta erişkin okuryazarlığının hızlı değerlendirilmesi) ölçeği ile değerlendirilerek, %44,7'si yetersiz, %49,3'ü kısıtlı SOY düzeyinde bulunmuştur. 16 Özdemir ve ark. 'larının da, yine üçüncü basamak bir sağlık kuruluşunda, 456 erişkin hasta (yaş ortalaması 36,2±12,6) üzerinde yaptıkları çalışmada benzer sonuçlara ulaşmışlardır.…”
Section: Bulgularunclassified